Divorce Problems and Community Social Capital in Realizing Family Resilience in Aceh - Zainuddin, Muslim; Mansari, Mansari; Filzah, Nadhilah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
Divorce is a matter that is always fascinating to explore within Islamic law since it affects not only legal but also social and cultural issues. Therefore, various ways are carried out by the community to suppress the divorce rate so that family resilience should be maintained. This study aims to discuss to proleptic divorce practices that occur in Aceh, community response, and the socio-capital in the form of traditional values and religious leaders in Acehnese society to realize family resilience. This is an empirical legal study employing a sociology of law methodology. Interviews and literature reviews were utilized as methods of data collection. The data demonstrated that social changes in Aceh contributed to an increase in divorce rates. The response of the community to divorce is litigation, peudame (reconciling), and non-litigation (through the court). Traditional and gampong (village) officials with cultural and legal authority, such as the keuchik(village head), tuha peut, head Jurong (neighborhood chief), and teungku imuem, are involved in the resolution of disputes. Meanwhile, divorces that cannot be handled by customary means will be moved to the Religious Courts. In the context of legal sociology theory, however, customary and cultural values as social capital in the form of support from traditional and religious leaders can help the maintenance of family resilience.